2014
DOI: 10.1111/myc.12211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of K101 Nail Solution on Trichophyton rubrum and Candida albicans growth and ultrastructure

Abstract: Summary K101 Nail Solution (trademarks Emtrixâ, Nalox TM , Naloc TM ) is a combination of propylene glycol, urea and lactic acid in a topical formulation for the treatment of nails affected by onychomycosis. The aim of this study was to investigate the Minimal Cidal Concentration (MCC) of K101 Nail Solution against Trichophyton rubrum and Candida albicans as well as the effect of K101 Nail Solution on the micromorphology of these fungi. The MCC of K101 Nail Solution against T. rubrum and C. albicans was 50% af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The role of acidity (low pH) in the pathogenesis of dermatophytes is complex [ 13 ]. Transmission electron microscopy has shown that many fungal cells were necrotic when T. rubrum or Candida albicans was treated for 60 min in direct contact with 50% K101 nail solution (Moberg Pharma, Bromma, Sweden), a topical formulation of pH 4 containing 50 g propylene glycol, 15 g lactic acid and 10 g urea [ 14 ]. The most prominent changes were observed with T. rubrum ; the cell wall was clearly damaged, the membrane was disrupted and the content in the cytoplasm was degraded.…”
Section: Resultsmentioning
confidence: 99%
“…The role of acidity (low pH) in the pathogenesis of dermatophytes is complex [ 13 ]. Transmission electron microscopy has shown that many fungal cells were necrotic when T. rubrum or Candida albicans was treated for 60 min in direct contact with 50% K101 nail solution (Moberg Pharma, Bromma, Sweden), a topical formulation of pH 4 containing 50 g propylene glycol, 15 g lactic acid and 10 g urea [ 14 ]. The most prominent changes were observed with T. rubrum ; the cell wall was clearly damaged, the membrane was disrupted and the content in the cytoplasm was degraded.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, farnesol modulated the morphogenesis of C. albicans through a downregulation of Saps 2, 4, 5, and 6 expressions (Décanis et al, 2011). However, Hultenby et al (2014) reported that treatment of C. albicans with a mixture of propylene glycol, lactic acid and urea resulted in certain ultrastructural changes but without a specific mode of action.…”
Section: Discussionmentioning
confidence: 99%
“…; Hultenby et al . ), assessing the morphology of untreated cells or of cells exposed to antifungal drugs. Oregano essential oil affected mainly the cell wall and the membranes of the yeast.…”
Section: Discussionmentioning
confidence: 99%